Cell wall modulation by drought and elevated CO2 in sugarcane leaves - Araujo, Alexandre Junio Borges; de Souza, Amanda Pereira; Pagliuso, Débora; de Medeiros Oliveira, Mauro; Navarro, Bruno Viana; Grandis, Adriana; Buckeridge, Marcos Silveira (Frontiers in Plant Science, 2025)
Climate change poses significant challenges to global agriculture, with elevated atmospheric CO2 (eCO2) concentrations and increased frequency of droughts affecting crop productivity. Understanding how economically important crops like sugarcane respond to these combined stresses is essential for developing resilient cultivars. This study explores the effects of eCO2 and drought stress on sugarcane growth and cell wall composition. Sugarcane plants were cultivated under CO2 treatments (390 ppm and 780 ppm) and subjected to drought stress. Leaf biomass, cell wall composition, and global transcriptome sequencing were analyzed. eCO2 (780 ppm) significantly increased leaf biomass by 64%, attributed to enhanced photosynthesis and water-use efficiency. Conversely, drought reduced leaf biomass by 45%, highlighting sugarcane’s sensitivity to water scarcity. When both conditions were combined, eCO2 mitigated drought’s negative impact, maintaining biomass at levels comparable to ambient conditions. Despite notable changes in biomass, cell wall biomass was only slightly affected. Under drought, a 14% reduction in cell wall biomass was observed alongside compositional changes, including reduced arabinosylation in glucuronoarabinoxylan (GAX). This alteration, supported by decreased xylan arabinosyl transferase (XAT) expression and reduced arabinose content, suggests stronger associations between GAX and cellulose, potentially enhancing drought tolerance by modifying cell wall rigidity and flexibility. Under eCO2, cell wall composition was altered, with reductions in glucose and uronic acid in specific fractions, indicating decreased mixed-linkage glucan (MLG) and pectin. These changes likely increased cell wall flexibility, supporting rapid growth. Combined eCO2 and drought treatments amplified specific modifications, such as enhanced fucosylation of xyloglucan (XG) and potential MLG expansion, both linked to stress adaptation. Overall, the findings underscore the critical role of cell wall plasticity in sugarcane’s response to abiotic stress. While eCO2 boosted growth and partially alleviated drought effects, structural changes in cell wall composition under these conditions further contribute to stress resilience, emphasizing the adaptive mechanisms of sugarcane to environmental challenges. This is the first report in which eCO2, and drought are combined to evaluate the response of sugarcane to the impact of climate changes.